Analisis Penilaian Kinerja (Keuangan dan Non Keuangan) Pada SPBU Coco Nomor 51.651.16 Raya Langsep Kota Malang Dengan Pendekatan Balance Scorecard - Mas Totok Illah; Efka Riza (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2021)
This study aims to analyze financial and non-financial performance at COCO SPBU NUMBER 51.651.16 RAYA LANGSEP MALANG CITY (also called COCO gas station 51.651.16). This performance appraisal analysis uses the Balanced Scorecard approach which includes a financial perspective, a customer perspective, an internal business process perspective as well as a growth and learning perspective. The data used in this study are primary and secondary data. The primary quantitative data were obtained through customer satisfaction surveys and interviews with the COCO gas station manager51,651.16. Qualitative secondary data obtained from gas station documents, internet, and literature studies, as well as consumer and employee satisfaction questionnaires were analyzed through validity and reliability tests. The success of COCO gas stations 51,651.16 used the Balance Scorecard approach from a financial perspective with a performance percentage of 87.5%. Perspective customers with a performance percentage of 87.5%, an Internal business perspective with a performance percentage of 100%, as well as a growth and learning perspective with a performance percentage of 90%.Keywords: financial perspective, customer perspective, internal business process perspective and growth and learning perspective.